Pericardial effusion with cystic mass - Coetzee, A.; Kyriakakis, C.G.; Herbst, P.G.; Doubell, A.F. (SA Heart Journal, 2017)
Patient with a 2-month history of exertional dyspnoea and a non-productive cough.